(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article examines the effective methods for developing pragmatic competence among upper-secondary school learners in English language classrooms. Pragmatic competence—understood as the ability to use language appropriately in social, cultural, and contextual situations—plays a central role in communicative competence but remains insufficiently addressed in traditional EFL instruction. The study analyzes existing scholarly sources, identifies methodological approaches relevant to today’s pedagogical context, and evaluates practical strategies such as role-play, scenario based learning, discourse analysis, authentic materials, and digital tools. Findings show that pragmatic-based instruction significantly improves learners’ sociolinguistic awareness, discourse management, and functional language use. The article concludes with pedagogical recommendations for English teachers and highlights the importance of integrating pragmatics systematically into curricula.